Sebuah Kajian Literatur: Perencanaan Pembelajaran Berdiferensiasi Sebagai Inovasi Pembelajaran di Sekolah Dasar - Anggita Widyasti; Sri Marmoah (PT. Saha Kreasi Indonesia, 2025)
This study examines differentiated instruction as an innovative strategy to address student diversity in elementary schools. The review explores its concepts, implementation, benefits, and challenges. A descriptive literature review method was applied by analyzing relevant scholarly articles published between 2019 and 2024. Data were collected through article searching, selection based on relevance and credibility, and analyzed using reduction, display, and conclusion drawing. The findings show that differentiated instruction is relevant for elementary education since it accommodates differences in students’ abilities, interests, and learning styles. It has been proven to enhance learning motivation, academic performance, and non-cognitive skills such as independence, self-confidence, social competence, and communication. Moreover, it fosters inclusive classrooms and reduces learning gaps caused by homogeneous practices. The study concludes that differentiation is an effective strategy for adaptive and student-centered learning. Further research is suggested to explore technology-based approaches or investigate its effectiveness in specific subjects.